USING INTERNET RESOURCES IN RUSSIAN LESSONS (Conferencea, 2024)
Innovative educational technology is a process, result and condition of joint creative activity of a teacher and a student, based on a certain philosophical concept and presupposing the mandatory achievement of planned goals in the course of the sequential implementation of a non-standard system of actions and operations. This topic is relevant and at the same time not sufficiently developed for use in an education setting as the aim of the article is to consider the features of studying the Russian language in modern conditions in institutions and study the influence of IT on learning motivation.